2015
DOI: 10.1007/s11948-015-9662-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Application in Europe: What Will Change with the New Regulation?

Abstract: The European framework surrounding clinical trials on medicinal products for human use is going to change as demonstrated by the large debate at European institutional level. One of the major challenges is to overcome the lack of harmonisation of clinical trial procedures among countries. This aspect is gaining more and more importance, considering the increasing number of multicentre and multinational studies. In this work, the actual European rules governing the Clinical Trial Application have been analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…However, as underlined in this work and in line with previous considerations [ 37 ], they have a poor legislative power and are implemented only partially in the regulation recently released [ 28 ].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, as underlined in this work and in line with previous considerations [ 37 ], they have a poor legislative power and are implemented only partially in the regulation recently released [ 28 ].…”
Section: Discussionmentioning
confidence: 58%
“…For paediatric trials, the assessment must take into account PDCO opinions on Paediatric Investigation Plans (PIPs) and must be carried out by ethics committees with paediatric expertise or seeking advice from experts in the field taking into account the risks and benefits of research and other aspects such as the study design, the use of placebo and the monitoring of safety during and after the trial. This represents an important achievement from the ethical point of view and in consideration of the protection of children’s rights [ 37 ]. However, uncertainties still remain on how national ethics committees and the PDCO will interact and what would happen if the PDCO and the ethics committee opinions differ [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…International cooperation for clinical trials that target small populations, such as rare disease or pediatric drug development, should be investigated further. Previous studies of EU-based trials have illustrated the importance of harmonization in clinical trial procedures where the trials conducted are necessary for pediatric clinical trials, given the rise of multicenter and multinational research [17]. It was reported that the key challenge these trials faced was overcoming the lack of harmonization of the status of several procedures across different countries.…”
Section: Future Steps For Pediatric Clinical Trialsmentioning
confidence: 99%
“…[6] The proportionality of acceptable and possible risk-to-benefit ratio is currently determined by a declaration of will of the research participant, i.e. constructs of informed consent [11,12,13,14].…”
Section: State Of Knowledgementioning
confidence: 99%